Proceedings of the Twenty-Ninth International Joint Conference on Artificial Intelligence 2020
DOI: 10.24963/ijcai.2020/530
|View full text |Cite
|
Sign up to set email alerts
|

On the Importance of Word and Sentence Representation Learning in Implicit Discourse Relation Classification

Abstract: Implicit discourse relation classification is one of the most difficult parts in shallow discourse parsing as the relation prediction without explicit connectives requires the language understanding at both the text span level and the sentence level. Previous studies mainly focus on the interactions between two arguments. We argue that a powerful contextualized representation module, a bilateral multi-perspective matching module, and a global information fusion module are all important to implicit dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Second, in most cases, jointly inferring multi-level labels (HierMTN-CRF-RoBERTa, OurEncoder+OurDecoder, LDSGM) performs better than separately predicting in BMGF-RoBERTa, Table 2: Comparison with recent models on the consistency among multi-level label predictions. We run the code of BMGF-RoBERTa (Liu et al 2020) and report the results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, in most cases, jointly inferring multi-level labels (HierMTN-CRF-RoBERTa, OurEncoder+OurDecoder, LDSGM) performs better than separately predicting in BMGF-RoBERTa, Table 2: Comparison with recent models on the consistency among multi-level label predictions. We run the code of BMGF-RoBERTa (Liu et al 2020) and report the results.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we report the label-wise F 1 scores for the second-level labels in Table 4. A closer look into the results reveals that though our LDSGM model outperforms BMGF-RoBERTa (Liu et al 2020) on most majority labels, the F 1 scores for three minority labels are still 0%. Besides, the BERT-based model (Kishimoto, Murawaki, and Kurohashi 2020) that small numbers of training examples are insufficient to optimize the huge amounts of parameters in these models.…”
Section: Performance On Minority Label Predictionsmentioning
confidence: 94%
See 1 more Smart Citation
“…For the classification subtasks, we use the BiMPM [31] multi-perspective symmetric matching model, originally proposed for sentence matching and used to extract implicit interactions between text spans [17]. In the BiMPM model, two textual inputs are encoded in the BiLSTM encoder and the generated vectors are matched in both directions on each time step.…”
Section: Models For Unlabeled Tree Construction and Discourse Relation Classificationmentioning
confidence: 99%
“…As claim representations { ← − H i } and { − → H i } from RoBERTa are not bidirectional, we need to combine them and control which of them matters more. The gated fusion (Liu et al, 2020) has been shown of a better mixture than the combination of multihead attention and layer normalization. We use it to maintain the powerful representative features and carry useful historical context information:…”
Section: Bidirectional Representation Fusionmentioning
confidence: 99%